First Detection of X-Ray Polarization from the Accreting Neutron Star 4U 1820−303 - Alessandro Di Marco; Fabio La Monaca; Juri Poutanen; Thomas D. Russell; Alessio Anitra; Ruben Farinelli; Guglielmo Mastroserio; Fabio Muleri; Fei Xie; Matteo Bachetti; Luciano Burderi; Francesco Carotenuto; et al. (The Astrophysical Journal Letters, 2023)
This paper reports the first detection of polarization in the X-rays for atoll-source 4U 1820−303, obtained with the Imaging X-ray Polarimetry Explorer (IXPE) at 99.999% confidence level (CL). Simultaneous polarimetric measurements were also performed in the radio with the Australia Telescope Compact Array. The IXPE observations of 4U 1820−303 were coordinated with Swift X-ray Telescope, Neutron Star Interior Composition Explorer, and Nuclear Spectroscopic Telescope Array aiming to obtain an accurate X-ray spectral model covering a broad energy interval. The source shows a significant polarization above 4 keV, with a polarization degree of 2.0% ± 0.5% and a polarization angle of −55° ± 7° in the 4–7 keV energy range, and a polarization degree of 10% ± 2% and a polarization angle of −67° ± 7° in the 7–8 keV energy bin. This polarization also shows a clear energy trend with polarization degree increasing with energy and a hint for a position-angle change of ≃90° at 96% CL around 4 keV. The spectro-polarimetric fit indicates that the accretion disk is polarized orthogonally to the hard spectral component, which is presumably produced in the boundary/spreading layer. We do not detect linear polarization from the radio counterpart, with a 3 σ upper limit of 50% at 7.25 GHz.